2013
DOI: 10.1097/psn.0b013e31828425db
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Closed Suction Surgical Drainage System

Abstract: Smaller drain reservoirs are more successful in generating a high initial suction than larger reservoirs, especially when the volume of fluid in the drain is relatively low. In all sizes of drains, compressing the sides of the reservoir is a far better technique for establishing negative pressure than pressing the bottom of the drain up toward the top.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Our conclusion supports the recommendations of other studies that bulbs should be emptied more frequently based on bulb filling. Carruthers et al, along with several other groups, have demonstrated similar findings that maximal pressures were generated when the bulb was empty and that negative pressure values decreased with bulb filling. Further supporting our recommendation, Yue et al demonstrated that accuracy of drainage volume decreases at extreme volumes .…”
Section: Discussionmentioning
confidence: 61%
“…Our conclusion supports the recommendations of other studies that bulbs should be emptied more frequently based on bulb filling. Carruthers et al, along with several other groups, have demonstrated similar findings that maximal pressures were generated when the bulb was empty and that negative pressure values decreased with bulb filling. Further supporting our recommendation, Yue et al demonstrated that accuracy of drainage volume decreases at extreme volumes .…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, when applying compression to the bulb drain, the drain should be fully compressed by squeezing with a fi st to generate negative pressure. 17 …”
Section: Maintaining Negative Pressure Of Collection Bulbsmentioning
confidence: 99%
“…These pressures were generated by squeezing the drainage bulb with a fi st to the point of full compression. 17 Carruthers et al 17 also explored the suction generated among drains of all sizes by different modes of compression. They compared suction pressure following drainage bulb compression using the squeeze method (compressing the sides of the bulb along its longest axis) and using the bottom-toward-top method (pushing the bottom of the drain toward the top) (see Figure).…”
Section: Maintaining Negative Pressure Of Collection Bulbsmentioning
confidence: 99%
See 2 more Smart Citations